Optimization Model of the Socio-Ecological-Economic Development of the Administrative Territory - MATVIEIEVA, Yuliia; MYROSHNYCHENKO, Iuliia; VALENKEVYCH, Larysa (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019DO - 10.14505//jemt.10.8(40).17, 2020)
In this paper, we contribute to the literature focusing on the development of methodical approach to the conducting of a comprehensive diagnostics of the state and level of the balance of the socio-ecological-economic system of the administrative territory, which, unlike existing ones, implies the determining of partial and integral indices of the socio-ecological-economic development, by comparing the existing and reference values of development of social, ecological and economic fields of activity. The article suggests the express diagnostics of the level of the socio-ecological-economic balance of the system on the basis of the graphic method, which, as a result, allows the forming of the optimization model of the socio-ecological-economic development of the administrative territory. The distribution of financial resources is proposed to be implemented on the basis of the disproportions in the development of social, environmental and economic fields of activity and allocation of financial resources, first of all, to those fields that provide the maintenance of the trajectory of balanced socio-ecological-economic development of administrative-territorial units.